Examining the Causal Inference of Leptin and Soluble Plasma Leptin Receptor Levels on Schizophrenia: A Mendelian Randomization Study - Chen, Guoqing; Wang, Qiuling; Xue, Ranran; Liu, Xia; Yu, Hao (Frontiers in Psychiatry, 2021)
Background: Observational studies that have supported the role of the leptin level in schizophrenia (SCZ) risk are conflicting. Therefore, we performed a two-sample Mendelian randomization (MR) analysis to investigate whether the circulating leptin and soluble plasma leptin receptor (sOB-R) levels play a causal role in SCZ risk. Methods: We first selected five independent single nucleotide polymorphisms (SNPs) associated with the circulating leptin level and three independent SNPs associated with the sOB-R level from two genome-wide association studies (GWASs) of European individuals. Then, we extracted their associations with SCZ using a large-scale GWAS that consisted of 40,675 patients with SCZ and 64,643 controls of European ancestry. We performed an MR analysis using the inverse variance weighting (IVW) method to examine the causal effect of leptin on SCZ risk. Moreover, we performed sensitivity analyses to verify our MR results using the weighted median and MR-Egger methods. Results: According to the IVW-method, genetically predicted circulating leptin levels were not associated with SCZ risk (OR=1.98, for per 1-SD unit increase in leptin level; 95% CI, 0.87–4.53; P = 0.10). In addition, the sOB-R level showed no causal effect on the SCZ risk using inverse variance weighting (OR=0.98 for per 1-SD unit increase in sOB-R level; 95% CI, 0.97–1.00; P = 0.06). Our sensitivity analyses results confirmed our MR findings. Conclusions: By estimating the causal effect of leptin on SCZ risk using the MR methods, we identified no effect of genetically predicted circulating leptin or the sOB-R level on SCZ. As such, our study suggests that leptin might not be a risk factor for SCZ.